2012
DOI: 10.2478/s11534-012-0101-4
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature measurements by infrared spectroscopy in CoFe2O4 ceramic

Abstract: Abstract:This paper presents results of new far-infrared and middle-infrared measurements (wavenumber range of 4000 -100 cm −1 ) of the CoFe 2 O 4 ceramic in the temperature range from 300 K to 8 K. The band positions and their shapes remain constant across the wide temperature range. The quality of the sample was investigated by X-ray, EDS and EPMA studies. The CoFe 2 O 4 retains the cubic structure (F − 3 ) across the temperature range from 85 K to 360 K without any traces of distortion. Based on current kno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
1
6
0
1
Order By: Relevance
“…Finally, the presence of small absorption broad band in the range 200 -300 cm -1 is assigned to the lattice vibration of the ferrite [27]. Fig.…”
Section: Ft-ir Spectramentioning
confidence: 83%
“…Finally, the presence of small absorption broad band in the range 200 -300 cm -1 is assigned to the lattice vibration of the ferrite [27]. Fig.…”
Section: Ft-ir Spectramentioning
confidence: 83%
“…Можно предполагать, что отклонение от правил отбо-ра и присутствие запрещенного фонона T 2g в спектрах поляризации a(bb)a, а также наличие фонона E g в спектрах a(bc)a вызваны особенностями обращенных шпинелей, а именно наличием ионов [Co/Ti] в октаэд-рических позициях. Следует отметить, что в литературе имеются неоднозначные трактовки наблюдаемых фонон-ных мод как в нормальных, так и в обращенных шпине-лях [13][14][15]. На температурных зависимостях спектров наблюдается сдвиг фононов в область высоких частот на 2−6 cm −1 , связанный с уменьшением роли ангар-монизма и тепловым сжатием решетки [16].…”
Section: экспериментальные результаты и их обсуждениеunclassified
“…FTIR spectra of spinel ferrites correspond only to T 1u and experimentally reflected in the form of four absorption bands in the range of 250À800 cm ¡1 . [18,19] FTIR spectra were recorded from 350 to 800 cm ¡1 (Figure 2). The spectra indicate presence of two primary absorption bands, v 1 and v 2 .…”
Section: Characterizationmentioning
confidence: 99%
“…So, the presence of the bands v 1sp and v 2sp reflects this complex interplay of the various factors discussed above and activation of silent spectral modes/splitting of absorption bands. In a comprehensive work reported by Bujakiewicz-Koronska et al,[18] silent modes are found to be activated in spinel ferrites. The additional absorption bands are due to lowering of symmetry and they correspond to A 2u , E u , and T 2u modes.…”
mentioning
confidence: 93%